ENHANCING DATA SECURITY: SECURE AND EXPRESSIVE ACCESS CONTROL FOR CLOUD STORAGE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In order to ensure the classification of reappropriated information while also providing adaptable information access to cloud clients whose information is not under their physical control, secure distributed storage is a growing cloud administration trend. One of the most promising methods for verifying the administration's certification is cypher text-policy attribute-based encryption (CP-ABE). Due to the inherent "win big or bust" unscrambling feature of CP-ABE, the adoption of CP-ABE may result in an inescapable security breach known as the abuse of access accreditation (for example, decoding privileges). Here, we focus on two key cases in which a cloud client's access qualification is abused by a semi-believed specialist. CryptCloud+, a distributed storage platform with white-box discernibility and review, is proposed as a way to limit the exploitation of the system. Additionally, we demonstrate the framework's usefulness by conducting studies.